(untitled) (Bangladesh Journal of Pharmacology, 2019)
The aim of the present study was to evaluate the hypoglycemic potential of Trixis angustifolia in alloxan-induced diabetic mice. An intragastric administration of the aqueous extract (50, 100 and 200 mg/kg) prepared from the aerial parts of T. angustifolia was evaluated. The treatment with the extract at 100 mg/kg produced a significant lowered (30.5%) of the blood glucose levels in diabetic mice after 15 days of daily oral administration. In addition, the extract induced a significant decrease in serum total cholesterol, low density lipoprotein whereas increased the high-density lipoprotein level. Additionally, the presence of alkaloids, cumarins, saponins, flavonoids and reducing sugars were identified in the extract. These findings provide a basis explaining the traditional folk medicine use of this plant as a hypoglycemic agent by the Mexican people. Video Clip of Methodology: 5 min 16 sec: Click to watch